2020
DOI: 10.1177/1048291120920553
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Impact of Frequent Short Training as an Enhancement of Annual Refresher Training

Abstract: Introduction of facilitated hands-on drills as often as monthly and the use of online modules prior to annual refresher training for emergency response teams were investigated through surveys and group discussions. This research explores how these drills are perceived by emergency response team members, emergency response team coordinators, instructors, and management at the company. Using these tools throughout the year, members of emergency response teams from automobile manufacturing facilities rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Certainty and exible work schedules boost staff motivation and increase productivity [31,32]. In times of low demand, time can be effectively used to provide staff with preparation or refresher training for the diverse roles they might play during the vaccination period and for team-building activities [33,34]. In other studies, [35,36] it has been found that during pandemic periods, staff are often assigned emergent roles for which they are less prepared, as also noted in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Certainty and exible work schedules boost staff motivation and increase productivity [31,32]. In times of low demand, time can be effectively used to provide staff with preparation or refresher training for the diverse roles they might play during the vaccination period and for team-building activities [33,34]. In other studies, [35,36] it has been found that during pandemic periods, staff are often assigned emergent roles for which they are less prepared, as also noted in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Certainty and flexible work schedules boost staff motivation and increase productivity [ 36 , 37 ]. During periods of low demand, it is recommended to utilize time effectively by providing staff with preparation or refresher training for the various roles they may need to fulfil during the vaccination period, as well as participating in team-building activities [ 38 , 39 ]. In other studies [ 40 , 41 ], during pandemic periods, staff are often assigned emergent roles for which they need more preparation, as also noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, refresher training should be conducted for the frontline workers to enhance their communication skills and understanding of the DHI as studies suggest that this would lead to increased confidence and information retention which would result in better work efficiency. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Further, refresher training should be conducted for the frontline workers to enhance their communication skills and understanding of the DHI as studies suggest that this would lead to increased confidence and information retention which would result in better work efficiency. 21 Technical difficulties may affect the quality and efficiency of work being done by the frontline workers. A significant number of the study participants reported frequent data sync and battery issues.…”
Section: Discussionmentioning
confidence: 99%